1993
DOI: 10.1182/blood.v81.2.412.412
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of viral hepatitis in a United States hemophilic population

Abstract: Hemophilia A and B patients seen at nine US regional treatment centers were tested for serologic markers of hepatitis B virus (HBV), hepatitis C virus (HCV), and hepatitis delta virus (HDV) during 1987 and 1988. Because human immunodeficiency virus (HIV) infection, a potentially confounding variable, was present in 53% of the group, the population was divided by HIV status for analysis purposes. In the HIV-positive group (N = 382), less than 1% had not been infected with HBV, HCV, or HDV, whereas 75% had evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(34 citation statements)
references
References 0 publications
4
29
1
Order By: Relevance
“…In addition, this cohort would have been the first to benefit from the screening of blood donors using the surrogate markers ALT (begun in late 1986) and anti‐HBc (begun in early 1987), testing that was associated with a markedly decreased risk of HCV infection from blood transfusions 33 . The higher prevalence of HCV that we observed among patients exposed to factor IX preparations than among those exposed to FVIII products in the late 1980s is consistent with other reports 24,33 and may be due to the slower development of effective virus‐inactivation processes for factor IX products.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, this cohort would have been the first to benefit from the screening of blood donors using the surrogate markers ALT (begun in late 1986) and anti‐HBc (begun in early 1987), testing that was associated with a markedly decreased risk of HCV infection from blood transfusions 33 . The higher prevalence of HCV that we observed among patients exposed to factor IX preparations than among those exposed to FVIII products in the late 1980s is consistent with other reports 24,33 and may be due to the slower development of effective virus‐inactivation processes for factor IX products.…”
Section: Discussionsupporting
confidence: 90%
“…The risk factors that were associated with markers of HBV or HCV infection among tested individuals in our cohort, including disease severity, HIV infection, and amount of clotting factor used, have been identified previously 7,22–25 . We found that the prevalence of markers of HBV infection and of HIV and HCV infection declined gradually and at a roughly similar rate among birth cohorts from 1973 to 1985.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Early studies using first‐generation assays have underestimated the prevalence of the infection in this group [912–13]. Later studies, that used second‐generation enzyme‐linked immunosorbent assay and various confirmatory tests, demonstrated 89% (649 of 727) anti‐HCV positivity in a heterogeneous group of patients from the United States and 98% (176 of 179) in Dutch haemophiliacs who had been exposed to large pool non‐virally inactivated coagulation factor concentrates [14,15]. Some patients seemed anti‐HCV positive in first‐generation tests, but were negative in subsequent more sensitive and specific tests [16].…”
Section: Prevalence Of Infectionmentioning
confidence: 99%
“…Due to plasma contamination many patients have been infected until the early 1990s with blood‐borne viruses such as HIV [11] and Hepatitis C [12]. However, at the Malmoe centre the last infection with HCV is dated to 1986.…”
Section: Introductionmentioning
confidence: 99%